Valvular heart disease and calcification in CKD: more common than appreciated. Issue 12 (21st July 2019) - Ureña-Torres, Pablo; D'Marco, Luis; Raggi, Paolo; García–Moll, Xavier; Brandenburg, Vincent; Mazzaferro, Sandro; Lieber, Ari; Guirado, Lluis; Bover, Jordi
Abstract: Ischaemic heart disease, sudden cardiac death and arrhythmias, heart failure, stroke and peripheral arterial disease make up >50% of the causes of death in advanced chronic kidney disease (CKD). Calcification of the vascular tree and heart valves is partially related to these complications and has received growing attention in the literature. However, the main focus of research has been on the pathophysiology and consequences of vascular calcification, with less attention being paid to valvular calcification (VC) and its impact on the survival of CKD patients. Although VC has long been seen as an age-related degenerative disorder with minimal functional impact, several studies proved that it carries an increased risk of death and clinical consequences different from those of vascular calcification. In dialysis patients, the annual incidence of aortic valve calcification is nearly 3.3% and the reported prevalence of aortic and mitral VC varies between 25% and 59%. Moreover, calcification of both valves occurs 10–20 years earlier in CKD patients compared with the general population. Therefore, the purpose of this review is to summarize the current knowledge on the pathophysiology and relevance of VC in CKD patients, and to highlight specific clinical consequences and potential therapeutic implications.